2022
DOI: 10.3329/bjms.v21i2.58064
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interaction with Children on Happiness among the Elderly: A Pilot Study

Abstract: Objective: Happiness is a crucial component of human lives. It is thus logical to assume that considering satisfaction and joy will produce profitable outcomes. The study intended to examine the effectiveness of interaction with children on happiness among the elderly. Methods: We chose 20 institutionalized elderly and assigned them randomly to experimental and control groups. We used the happiness rating scale to test the happiness levels among the elderly. We chose children for interaction based on their att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A regression analysis based on an assessment of six domains of filial piety—respect, happiness, care, greeting, obedience, and support—showed that lower scores on filial expectations significantly increased the risk of depressive symptoms among older adults and that these expectations may be related to SWB ( 25 ). It was also found that interaction with children was useful in improving older parents' wellbeing and that designing and implementing programs to connect with children could help improve the happiness, joy, and satisfaction of older adults in institutions ( 26 ). Also important is that China is transitioning from a child-centered to a parent-centered approach, which has increased the wellbeing of rural older adults by 28% ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…A regression analysis based on an assessment of six domains of filial piety—respect, happiness, care, greeting, obedience, and support—showed that lower scores on filial expectations significantly increased the risk of depressive symptoms among older adults and that these expectations may be related to SWB ( 25 ). It was also found that interaction with children was useful in improving older parents' wellbeing and that designing and implementing programs to connect with children could help improve the happiness, joy, and satisfaction of older adults in institutions ( 26 ). Also important is that China is transitioning from a child-centered to a parent-centered approach, which has increased the wellbeing of rural older adults by 28% ( 27 ).…”
Section: Introductionmentioning
confidence: 99%